Anterior fontanelle closure and diagnosis of non-syndromic craniosynostosis: a comparative study using computed tomography - Leopoldo Mandic Ferreira Furtado; José Aloysio da Costa Val Filho; Letícia Silveira Freitas; Aieska Kellen Dantas dos Santos (Elsevier, 2022)
Objective: Suspicion of early anterior fontanel (AF) closure is a common reason for referral to a pediatric neurosurgeon because of the suspected increased risk of developing craniosynostosis (CS) in spite of the absence of evidence in the literature. The aim of this study was to analyze the association between AF closure and the diagnosis of non-syndromic CS in Brazilian children. Methods: An observational and case-cohort study was conducted to compare the incidence of closed AF between healthy children (group 1) and children diagnosed with non-syndromic CS (group 2) at a pediatric neurosurgery referral center. The accuracies of completely closed AF and diagnosis of CS were assessed. Results: High-resolution three-dimensional reconstruction computed tomography scans were obtained for 140 children aged < 13 months, of whom 62.9% were boys and 37.1% were girls (p < 0.001). The most common types of non-syndromic CS were trigonocephaly (34, 48%) and scaphocephaly (25, 35.7%). Closed fontanel (27, 38.6%) was observed in both groups, and a sensitivity of 36.1%, specificity of 72%, the positive predictive value of 59%, and negative predictive value of 51% were observed in the patients diagnosed with CS when AF closure occurred before the age of 6 months. Conclusion: The results of this comparative study of AF closure and CS diagnosis suggest that early AF closure does not imply a diagnosis of CS. Pediatricians should be aware of the risk of misdiagnosis of CS in cases with a widely open AF in spite of the presence of CS.